Ab initio conformational study of caffeic acid - VanBesien, E. (2003)
A complete conformational analysis of caffeic acid, a phenolic derivative with well known antioxidant properties, was carried out by ab initio calculations, at the density funtional theory (DFT) level. Fourteen different conformers were obtained, the most stable ones being planar, as the conformational preferences of this molecule were found to be mainly determined by the stabilising effect of [pi]-electron delocalisation. Harmonic vibrational frequencies, as well as potential energy profiles for rotation around several bonds within the molecule, were also calculated.